Current understanding of iberiotoxin-resistant BK channels in the nervous system - Wang, Bin; Jaffe, David B.; Brenner, Robert (Frontiers in Physiology, 2014)
While most large-conductance, calcium- and voltage-activated potassium channels (BK or Maxi-K type) are blocked by the scorpion venom iberiotoxin, the so-called “type II” subtype has the property of toxin resistance. This property is uniquely mediated by channel assembly with one member of the BK accessory β subunit family, the neuron-enriched β4 subunit. This review will focus on current understanding of iberiotoxin-resistant, β4-containing BK channel properties and their function in the CNS. Studies have shown that β4 dramatically promotes BK channel opening by shifting voltage sensor activation to more negative voltage ranges, but also slows activation to timescales that theoretically preclude BK ability to shape action potentials (APs). In addition, β4 membrane trafficking is regulated through an endoplasmic retention signal and palmitoylation. More recently, the challenge has been to understand the functional role of the iberiotoxin-resistant BK subtype utilizing computational modeling of neurons and neurophysiological approaches. Utilizing iberiotoxin-resistance as a footprint for these channels, they have been identified in dentate gyrus granule neurons and in purkinje neurons of the cerebellum. In these neurons, the role of these channels is largely consistent with slow-gated channels that reduce excitability either through an interspike conductance, such as in purkinje neurons, or by replacing fast-gating BK channels that otherwise facilitate high frequency AP firing, such as in dentate gyrus neurons. They are also observed in presynaptic mossy fiber terminals of the dentate gyrus and posterior pituitary terminals. More recent studies suggest that β4 subunits may also be expressed in some neurons lacking iberiotoxin-resistant BK channels, such as in CA3 hippocampus neurons. Ongoing research using novel, specific blockers and agonists of BK/β4, and β4 knockout mice, will continue to move the field forward in understanding the function of these channels